Pengaruh Ekspor Batu Bara dan Kurs Terhadap Pendapatan Devisa Negara Indonesia - Irfan Liandy; Sanusi Gazali Pane (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
Foreign exchange earnings are very important to maintain economic stability and state development. This study aims to analyze the effect of coal exports and exchange rate changes on Indonesia's foreign exchange earnings due to the urgent need to understand the impact of coal exports and exchange rate changes on foreign exchange earnings. This research will use a quantitative approach using time series data from 2004 to 2022 from the Central Bureau of Statistics (BPS). This study uses multiple linear regression using the Eviews program. The results show that, while coal exports have a significant negative impact on Indonesia's foreign exchange earnings, the exchange rate has an insignificant positive impact on it. The F-test (simultaneous) confirms that both have a significant effect on Indonesia's foreign exchange earnings.